An Intelligent Independence Ecosystem Framework for Enhancing Indonesia’s Naval Defense Industrial Capability - Jupriyanto Jupriyanto; Sri Yanto; Mukhtiali Mukhtiali; Ade Mirza Roslinawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Indonesia’s naval defense industry plays a critical role in safeguarding the world’s largest archipelagic state. However, it remains highly dependent on foreign suppliers for mission-critical warship technologies, creating strategic vulnerabilities to geopolitical disruptions and supply chain uncertainty. This study aims to identify critical capability gaps within Indonesia’s warship industrial ecosystem and develop an Intelligent Independence Ecosystem Framework to strengthen long-term industrial resilience. A qualitative case study with embedded mixed-method data collection was employed using Product Breakdown Structure (PBS) analysis, supply chain mapping, legal classification based on Law Number 16 of 2012, and strategic evaluation through SWOT, Internal Factor Evaluation (IFE), and External Factor Evaluation (EFE) matrices. The findings reveal that Tier 2 represents the principal structural bottleneck, particularly in propulsion systems, combat management systems, sonar, and advanced weapon systems, while platform-related capabilities exhibit substantially higher localization potential. The industry achieved an IFE score of 2.20 and an EFE score of 2.35, positioning it in Cell V (Hold and Maintain) of the IE Matrix. Accordingly, this study proposes the Intelligent Independence Ecosystem Framework, which integrates progressive localization, diversified international technology partnerships, and strengthened research, industrial collaboration, and human capital development to improve the resilience, competitiveness, and long-term sustainability of Indonesia’s naval defense industry